Immune Correlates of Natural HIV Elite Control and Simultaneous HCV Clearance—Supercontrollers - Dominguez-Molina, Beatriz; Ferrando-Martinez, Sara; Tarancon-Diez, Laura; Hernandez-Quero, Jose; Genebat, Miguel; Vidal, Francisco; Muñoz-Fernandez, Mª Angeles; Leal, Manuel; Koup, Richard; Ruiz-Mateos, Ezequiel (Frontiers in Immunology, 2018)
HIV-elite controllers are a minority group of HIV-infected patients with the ability to maintain undetectable HIV viremia for long time periods without antiretroviral treatment. A small group of HIV-controllers are also able to spontaneously clear the hepatitis C virus (HCV) whom we can refer to as “supercontrollers.” There are no studies that explore immune correlates looking for the mechanisms implicated in this extraordinary phenomenon. Herein, we have analyzed HCV- and HIV-specific T-cell responses, as well as T, dendritic and NK cell phenotypes. The higher HCV-specific CD4 T-cell polyfunctionality, together with a low activation and exhaustion T-cell phenotype was found in supercontrollers. In addition, the frequency of CD8 CD161high T-cells was related with HIV- and HCV-specific T-cells polyfunctionality. Interesting features regarding NK and plasmacytoid dendritic cells (pDCs) were found. The study of the supercontroller's immune response, subjects that spontaneously controls both chronic viral infections, could provide further insights into virus-specific responses needed to develop immunotherapeutic strategies in the setting of HIV cure or HCV vaccination.